Preview of highlighted presentations from the European Respiratory Society’ clinical assembly - Kahn, Nicolas; Vanfleteren, Lowie E. G. W.; Kaltsakas, Georgios; Andrianopoulos, Vasileios; Gompelmann, Daniela; de Jong, Corina; Herth, Felix J. F. (Journal of Thoracic Disease, 2018)
This paper highlights a selection of abstracts that will be presented at the 2018 European Respiratory Society (ERS) International Congress in Paris. The abstract were submitted through the five different groups of our society largest assembly, the clinical assembly (assembly 1).